PEMBERDAYAAN PEDAGANG PASAR KREMPYENG DI TENGAH PANDEMI COVID-19: PEMBERDAYAAN PEDAGANG PASAR KREMPYENG DI TENGAH PANDEMI COVID-19 - Siti Alliyah; Maslichan Maslichan (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
The Covid-19 pandemic that has hit all countries since the beginning of 2020 has caused all sectors of life, especially the economy, to experience a very large impact. In connection with the existence of WFH and social distancing, the movement of the community in life is slow because with WFH people cannot leave the house and with social distancing people are prohibited from carrying out activities that are gathering or grouping. Rembang city is one of the areas in Central Java which is included in the red zone, because of the presence of several people who were positive for the Covid-19 virus. So that people also do WFH and social distancing. One of the villages that experienced the impact of WFH and social distancing is Jolotundo village. One of the community activities affected by the covid-19 virus is the activity of the Jolotundo village community “pasar krempyeng”. So that the STIE YPPI Rembang service team is motivated to solve partner problems, where the focus of our activities is so that the “pasar krempyeng” trader group has a new business, where the new business can be carried out both on the production and marketing side. Methods of implementing activities that have been carried out include: counseling, management training and practice of making herbal medicine. The results of community service activities in Jolotundo village, including; There are group participants who open a new business (herbal drink), there is an attractive packaging that supports the marketing program.